Ethnobotanical and ecological study of medicinal plants of mangroves in Siak District, Riau Province, Indonesia - Salmiah Safitri; Aras Mulyadi; Nofrizal Nofrizal; Dessy Yoswaty (Pelantar Press, 2024)
The mangrove forest in Kayu Ara Permai Village, Sungai Apit, Siak Regency, Riau Province, Indonesia, is a mangrove forest managed by the local community as the